Vai trò của lãnh đạo đổi mới trong chuyển hóa năng lực thành hiệu suất làm việc - Trần Yến Hảo, Hảo; Lâm Quốc , Bảo; Phạm , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
In the context of a rapidly changing market, both organizational practices and individual capabilities play a crucial role in adapting to and responding to change. Based on social learning theory, this study examines the impact of learning organizations on employees’ self-efficacy and employee performance, while also considering the moderating role of innovative leadership. Data were collected from 338 employees across various industries in Vietnam. The PLS-SEM analysis indicates that learning organizations positively influence self-efficacy, while both self-efficacy and innovative leadership significantly affect employee performance. Notably, innovative leadership serves as a critical moderator, facilitating the transformation of individual capabilities into actual performance within a learning organizational context. This study contributes to the extension of social learning theory in the Vietnamese business environment and offers managerial implications for fostering a learning culture and leveraging innovative leadership to enhance employee performance